Atp-emtp investigation of adaptive algorithms for distance protection of double circuit lines - Izykowski, J.; Bozek, M. (Видавництво Національного університету «Львівська політехніка», 2007)
Подано нові адаптивні алгоритми, які дають змогу компенсувати вплив реактансу під час коротких замикань на двоколових лініях. The paper presents new adaptive algorithms that allow compensating for the reactance effect in case of faults on double circuit lines. The algorithms calculate the shift vector that changes the position of the relay characteristic on R–X plane. Standard and complete availability of measurements at one end is considered. Results of ATP-EMTP simulations are presented and discussed.